Topical treatment of impetigo with ozenoxacin in children. - Gelmetti, C.; Boccaletti, V.; Amadori, A.; Bosis, S. (European Journal of Pediatric Dermatology, 2020)
Impetigo, in the bullous and non-bullous variants, is a common and frequent acute infection of the superficial skin, caused by Staphylococcus aureus or Streptococcus pyogenes. It is particularly frequent in children, with a tendency to self-resolution in about two or three weeks in some cases. The recent intersociety Consensus (Italian Society of Pediatrics, Italian Society of Pediatric Infectious Diseases, Italian Society of Pediatric Dermatology, Italian Society of Preventive and Social Pediatrics, Italian Federation of Pediatricians) recommends topical treatment to limit its extension and avoid recurrence by reserving the addition of systemic therapy in plurifocal or complicated cases. A group of pediatricians and one dermatologist expert in impetigo management offers a focus on the disease and on new topical therapy with ozenoxacin 1%. The latter is an effective and safe treatment from 6 months of age even in the presence of the current antibiotic resistance phenomena.